Socio-Economic Transformation and Erosion of Cultural Identity in The Morowali Nickel Industry Area: A Case Study of The Bungku-Bahodopi Community, Central Sulawesi - Helmina Kastanya; Abd. Azis; Titih Nursugiharti; Erniati; Erwin Syahputra Kembaren; Janeke Peggy Slippy; Maria Christina Anandya Prijandoko (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
The massive expansion of the nickel industry in Morowali Regency, Central Sulawesi, has triggered profound socio-economic and socio-cultural transformations among the Bungku indigenous community in Bahodopi District. Using qualitative ethnographic approaches, historical analysis, and document review , this research examines how extractive industrialization systematically reconfigures traditional livelihoods, disrupts ecological governance, threatens the Bungku language, and erodes intangible cultural heritage. The findings reveal a development paradox: while macroeconomic indicators show significant growth through the presence of the Indonesia Morowali Industrial Park (IMIP) with a total investment of over USD 34.3 billion, the indigenous community experiences simultaneous marginalization through the eviction of living space, alienation of livelihoods, extinction of language, and erosion of rituals. This transformation shifts the community from a self-sufficient maritime-agrarian economy based on local ecological wisdom to an industrial periphery dependent on a wage system. This article argues that sustainable industrial development requires culturally sensitive policies, cultural heritage buffer zones, linguistic revitalization programs, and genuine Free, Prior, and Informed Consent (FPIC) mechanisms to prevent irreversible cultural loss.